An Integrative Approach to Dynamic Processes in Reverse Osmosis Desalination - Akele, Omomayowa (2022)
The reverse osmosis membrane module is an integral element of a desalination system as it determines the overall performance of the desalination plant. The fraction of clean water that can be recovered via this process is often limited by salt precipitation. It has become apparent that precipitation plays a critical role in the sustainability of reverse osmosis desalination. Hence, the main objective that guides this research is unravelling some of the mysteries associated with precipitation, whilst considering it in the context of the other dynamic processes at work.